2005
DOI: 10.1128/jcm.43.10.4930-4942.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Pseudallescheria boydii Species Complex: Proposal of Two New Species

Abstract: Pseudallescheria boydii (anamorph Scedosporium apiospermum) is the species responsible for human scedosporiosis, a fungal infection with a high mortality rate and which is difficult to treat. Recently, it has been demonstrated that high genetic variation exists within this species. We have performed a morphological and molecular study involving numerous strains of clinical or environmental origins and from different countries. The analysis of partial sequences of the ␤-tubulin (two loci) and calmodulin genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
246
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(257 citation statements)
references
References 18 publications
5
246
2
4
Order By: Relevance
“…In line with previously reported genetic variability in the S. apiospermum/P. boydii species complex (30-32), we observed 2 distinct ITS-RFLP patterns among S. apiospermum isolates, showing the presence of the newly described species S. aurantiacum (11). Notably, we have identifi ed by ITS sequencing that S. aurantiacum comprised 45% of the current collection of Australian "S. apiospermum" isolates and documents genetic variability within S. aurantiacum.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In line with previously reported genetic variability in the S. apiospermum/P. boydii species complex (30-32), we observed 2 distinct ITS-RFLP patterns among S. apiospermum isolates, showing the presence of the newly described species S. aurantiacum (11). Notably, we have identifi ed by ITS sequencing that S. aurantiacum comprised 45% of the current collection of Australian "S. apiospermum" isolates and documents genetic variability within S. aurantiacum.…”
Section: Discussionsupporting
confidence: 73%
“…Given that S. aurantiacum is phylogenetically more closely related to S. apiospermum than to S. prolifi cans (11,33; current study), this result was unexpected. It may be due to different evolutionary pressures acting on the 3 different species or the relatively small numbers of S. aurantiacum isolates studied to date.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…recent studies have shown that b-tubulin is a good target for identification of opportunistic moulds such as Aspergillus, Penicillium, Scedosporium and Phaeoacremonium Essakhi et al, 2008;Gilgado et al, 2005;Mostert et al, 2005;Serra & Peterson, 2007;Staab et al, 2009). It is also well documented that translation elongation factor is the best marker for species identification in Fusarium (Geiser et al, 2004;O'Donnell, 2000).…”
Section: Differentiation Of M Canis and Its Close Relativesmentioning
confidence: 99%
“…and Scedosporium sp. cause human scedosporiosis, a fungal disease difficult to treat with a high mortality rate (16,17).…”
Section: Introductionmentioning
confidence: 99%